Identifying the value of RVEF for the prediction of major cardiovascular outcomes: a study of 7, 131 patients undergoing cardiovascular magnetic resonance imaging. (25th November 2020) - Purmah, Y; Lei, L; Dykstra, S; Labib, D; Mikami, Y; Satriano, A; Feutcher, P; Fine, N; Gaztanaga, J; Howarth, A; Heydari, B; Merchant, N; et al.
Abstract: Background: Right ventricular (RV) function remains poorly recognized for its value in predicting cardiovascular events at a population level. Cardiovascular Magnetic Resonance (CMR) imaging is the gold standard for RV assessment. Purpose: To define the independent prognostic value of RVEF for the prediction of major adverse cardiovascular events (MACE) as primary outcome in patients with known or suspected cardiovascular disease. Methods: Data was obtained from the Cardiovascular Imaging Registry of Calgary (CIROC). Patients underwent standardized CMR imaging protocols and analysis. Clinical events were identified from administrative data. Results: 7, 131 patients were included. 870 primary outcome events occurred over 2.5 years follow-up. RVEF provided equivalent predictive utility versus LVEF (Table 1). There was an increase in events with worsening severity of RVEF (Figure 1), with a significant "threshold-effect" at an RVEF of 40%. Conclusions: RVEF is a strong and independent predictor of MACE at a population level. Funding Acknowledgement: Type of funding source: None